2021
DOI: 10.4081/oncol.2021.510
|View full text |Cite
|
Sign up to set email alerts
|

Management of COVID-19 in cancer patients receiving cardiotoxic anti-cancer therapy. Future recommendations for cardio-oncology

Abstract: Cardiotoxicity induced by anti-cancer treatment has become a significant threat as the number of cardiotoxic anti-cancer agents is growing. Cancer patients are at an increased risk of contracting coronavirus disease 2019 (COVID-19) because of immune suppression caused by anti-cancer drugs and/or supportive treatment. Deterioration in lung functions due to COVID-19 is responsible for many cardiac events. The presence of COVID-19 and some of its treatment modalities may increase the chance of cardiotoxicity deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Recent studies reported that people with gastrointestinal disorders also are at increased risk of complications due to COVID-19 [ 140 ]. Additionally, some of the drugs used to treat COVID-19 have been found to have adverse effects on the cardiac system [ 141 , 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that people with gastrointestinal disorders also are at increased risk of complications due to COVID-19 [ 140 ]. Additionally, some of the drugs used to treat COVID-19 have been found to have adverse effects on the cardiac system [ 141 , 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…Childhood cancer survivors are also at increased risk of cardiovascular complications in their adulthood [ 43 ]. A newly emerged challenge is the management of COVID-19 in cancer patients receiving cardiotoxic antineoplastics in whom deteriorated lung function may be responsible for many additional cardiac events [ 156 ]. Thus, prophylactic intervention is even more critical to prevent cardiotoxicity in this group.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%